MOTIVATIONAL FACTORS OF STUDENTS IN CHOOSING JAPANESE LITERATURE STUDY PROGRAM AT A PRIVATE UNIVERSITY IN BANDUNG - Musyaafa, Muhammad Faiz Khoerul; Setiana, Soni Mulyawan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
During learning a foreign language, motivation is really essential, particularly Japanese. A student who wants to perform well will require more motivation to obtain the necessary results. Therefore, the goal of this study is to find out why students chose the Japanese Literature Study Program. This study used a quantitative descriptive research approach to discover the variables that influence students’ decisions. Thirty first-year students participated in this study, which included questions regarding a range of topics, including family history, future goals, incentive to live in one’s region, desire to visit Japan, and reputation of the university. As the survey’s results showed, these elements were crucial in helping students decide decisions. The students discussed their interests in pursuing jobs in fields utilizing the language, teaching or lecturing, and working for Japanese firms. They also considered the university’s excellent standing while making their decisions.